General theory of implicit will: Comparative Study - العبودي, عباس زبون; يوسف, كاظم حمادي (Journal of Legal Sciences, 2019)
In accordance with the principle of consensually, contractors have full freedom to express their will. The law does not require that the expression be by a particular means or form, as may be expressly expressed by the will, so the expression of will may be implicit. The general rule is that the parties have the freedom to freely determine the content of the contract Within the limits of the rules that regulate and regulate this will, the implied will or implied expression of will is a positive course of expression of will, but does not directly indicate the truth of the intended meaning, but the circumstances of the case allow weighting of the intended meaning to other possible meanings, In other words, a means or an appearance taken by a person is not in itself a subject to reveal the will, but it can not be explained without assuming that this will exists. The special contractual circumstances between the parties can only be interpreted as an expression of will. The obvious effect in all stages of the contract, from the negotiation stage until the end of the contract. There is no general theory of implicit will to define its definition, its characteristics and conditions to influence the contract, and distinguish it from other legal situations. The legal effect of expression Implicit of the will is no less important than the effect of express expression.